2020
DOI: 10.1002/anie.202002029
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy Engineering of Iron‐Doped W18O49 Nanoreactors for Low‐Barrier Electrochemical Nitrogen Reduction

Abstract: The electrochemical nitrogen reduction reaction (NRR) is a promising energy-efficient and low-emission alternative to the traditional Haber-Bosch process. Usually, the competing hydrogen evolution reaction (HER) and the reaction barrier of ambient electrochemical NRR are significant challenges, making a simultaneous high NH 3 formation rate and high Faradic efficiency (FE) difficult. To give effective NRR electrocatalysis and suppressed HER, the surface atomic structure of W 18 O 49 , which has exposed active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(144 citation statements)
references
References 58 publications
(22 reference statements)
2
142
0
Order By: Relevance
“…Thus, the exploration of efficient catalysts for NRR has drawn particular attraction in recent years. [ 5 ] By far, a number of catalysts that are based on metals (e.g., Ru, [ 6 ] Pd, [ 7 ] and Au [ 8 ] ), oxides (e.g., Fe 2 O 3 /carbon nanotube, [ 9 ] W 18 O 49 , [ 10 ] and BiOBr nanosheets [ 11 ] ), sulfides (e.g., FeMoS [ 12 ] ), black phosphorus, [ 13 ] nitrides (e.g., C 3 N 4 [ 14 ] and MoN [ 15 ] ), carbides (MoC [ 16 ] ), MXenes, [ 17 ] and single atoms (e.g., Mo, [ 18 ] B, [ 19 ] W, [ 20 ] and Ru [ 21 ] ) have been investigated.…”
Section: Figurementioning
confidence: 99%
“…Thus, the exploration of efficient catalysts for NRR has drawn particular attraction in recent years. [ 5 ] By far, a number of catalysts that are based on metals (e.g., Ru, [ 6 ] Pd, [ 7 ] and Au [ 8 ] ), oxides (e.g., Fe 2 O 3 /carbon nanotube, [ 9 ] W 18 O 49 , [ 10 ] and BiOBr nanosheets [ 11 ] ), sulfides (e.g., FeMoS [ 12 ] ), black phosphorus, [ 13 ] nitrides (e.g., C 3 N 4 [ 14 ] and MoN [ 15 ] ), carbides (MoC [ 16 ] ), MXenes, [ 17 ] and single atoms (e.g., Mo, [ 18 ] B, [ 19 ] W, [ 20 ] and Ru [ 21 ] ) have been investigated.…”
Section: Figurementioning
confidence: 99%
“…Refilling the anion vacancies with heteroatoms or atomic metal species is not only a feasible and efficient method to improve the stability, but also a potential strategy to further enhance the catalytic performance. [ 16,89–91 ]…”
Section: Anion Defects In Transition Metal Compounds For Electrocatalmentioning
confidence: 99%
“…Transition metal‐based materials such as Fe, Co, Ni, Mn, and Mo oxides/hydroxides and their composites are promising catalysts for various electrochemical reactions, and defects such as anion (O, S, and P) and cation (Fe, Co, and Ni) vacancies could serve as the active sites to promote the electrocatalysis. [ 15–17 ] It is revealed that defects in metal complexes could improve the electrical conductivity, charge redistribution, and optimize their adsorption energy and band structures, [ 18–20 ] thus favorable for various electrochemical reactions. As a booming area, researches on defective transition metal‐based catalysts have received extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…As the ionic radius increased from Yb to Nd, the bond length of Ru-O was elongated, which weakened the bonding strength of Ru-O and resulted in increased defective oxygen concentration. To keep the material electrically neutral, the average valence state of Ru decreased with the increase of defective oxygen [46].…”
Section: Science China Materialsmentioning
confidence: 99%